Career profiles: Career entrenchment or adaptation to change? - Oliveira,Lucília Cardoso (2020)
The rapid development of societies and the transformation of labour markets and organizations requires more dynamic careers nowadays. Thus, based on the career profiles described by Carson, Carson, Phillips and Roe (1996) and the association of career entrenchment and career satisfaction, we identified in this study, which career profiles currently exist. The cross-reference of data, with organizational commitment, career commitment and turnover intention, allowed to characterize each profile and the factors that weigh on the decision to stay or change career, keeping or not a positive attitude. We perform a cluster analysis using the K-means method, in a sample of 386 subjects. The results came across a new career profile, called transactional career, which might reflect that careers are currently more active and less stable. In the end, the results and the theoretical and practical implications are being discussed.